Praise - Cate, Sara (Cate, Sara. Salacious Players' Club, 2023)
"Broken down by her emotionally neglectful ex, all Charlie Underwood wants is someone to tell her she's good enough. Then she stumbles into a new job with a boss who brings her to her knees--literally. As an owner of the Salacious Players' Club, Emerson Grant knows exactly what he wants and isn't shy about his particular tastes. But when he mistakes Charlie for a candidate to be his new submissive instead of his son's ex-girlfriend, he immediately tries to correct the situation. He offers Charlie a job as his secretary and nothing more... Yet now that Charlie has seen a glimpse of what can happen when she's honest about what she wants, she makes it clear that all she wants is Emerson. He might be twice her age and her ex-boyfriend's dad, but he's also the only man who can give her everything she desires."--Page 4 of cover.